Clinical Features and Prognoses of IgG4-Positive and IgG4-Negative Lacrimal Lymphomas - Rui Liu; Jinjin Wang; Nan Wang; Jing Li; Xin Ge; Jingxue Zhang; Jianmin Ma (Frontiers in Oncology, 2021)
Purpose: The clinical characteristics and prognoses of immunoglobulin G4-positive (IgG4+) and IgG4-negative (IgG4−) lacrimal lymphomas were comparatively analyzed to screen for clinical indicators with differential diagnostic significance.Methods: This was a retrospective and single-center clinical study. From June 2011 to June 2018, clinical data of 39 patients with lacrimal lymphoma, diagnosed by histopathology were collected from the Department of Ophthalmology, Beijing Tongren Hospital, Capital Medical University.Results: According to inclusion and exclusion criteria, 30 (76.9%) were in the IgG4− group and 9 (23.1%) were in the IgG4+ group. In the IgG4+ group, the sex ratio of male to female was 2:1 and the mean age was 56.67 ± 13.29 years old. In the IgG4− group, the sex ratio of male to female was 3.29:1 and the mean age was 61.47 ± 12.87 years old. Statistical analysis of the clinical indicators showed significant differences between the two groups in affected eye, preoperative history of glucocorticoids, ocular nerve thickening, the expression of serum IgG4 and prognosis (P < 0.05). There was no significant statistical difference in laboratory indicators between the two groups, including C3, C4, RF, ASO, CRP, IgA, IgM, IgG, IgG1, IgG2, and IgG3 (P > 0.05). The event-free cumulative percentages at 3 and 5 years for the 39 lacrimal lymphomas were 81.1 and 62.4%, respectively, with recurrence and death as end events. In 34 lacrimal gland MALT lymphoma cases, the event-free cumulative percentages at 3 and 5 years were 84.4 and 69.1%, respectively. In the IgG4+ and IgG4− groups, the event-free cumulative percentages at 3 years were 75.0 and 87.7%, respectively. The event-free cumulative percentage at 5 years was 62.6% in the IgG4-group and insignificant in the IgG4+ group. There was no statistical difference in event-free cumulative percentage between the two groups (P = 0.983).Conclusion: The pathogenesis and disease characteristics of IgG4-positive lacrimal lymphoma may differ from IgG4-negative lacrimal lymphoma, but the positive expression of IgG4 may not have significant influence on the recurrence of lacrimal lymphoma.